1983
DOI: 10.1073/pnas.80.14.4359
|View full text |Cite
|
Sign up to set email alerts
|

Identification of homo-oligomers as potential intermediates in acetylcholine receptor subunit assembly.

Abstract: We have examined the sedimentation behavior, on sucrose density gradients, of acetylcholine receptor (AcChoR) subunits synthesized in vitro and integrated into heterologous rough microsomal membranes. In media containing nondenaturing detergents such as Triton X-100 or deoxycholate, the subunits appear to self-associate although, as previously reported, no heterologous interactions were detected. The sedimentation profiles assume a broad distribution in the region of 7-13 S. However, the peak fractions occupy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
1

Year Published

1984
1984
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 30 publications
1
8
1
Order By: Relevance
“…1 D), a 6S sedimentation profile was still obtained. Our 6S profile differs from those obtained by Anderson and Blobel (1983) who found that after synthesis in a cell-free translation system, Torpedo subunits sedimented broadly from ~7 to 13S with a peak at ~9.5S. Using conditions similar to those of the cell-free study (same detergent, buffers, and gradients), we typically observed a 6S sedimentation peak for Torpedo subunits and only obtained peaks >7S if the detergent to protein ratio was reduced (not shown); presumably this is due to insufficient solubilization.…”
Section: (G)contrasting
confidence: 99%
See 1 more Smart Citation
“…1 D), a 6S sedimentation profile was still obtained. Our 6S profile differs from those obtained by Anderson and Blobel (1983) who found that after synthesis in a cell-free translation system, Torpedo subunits sedimented broadly from ~7 to 13S with a peak at ~9.5S. Using conditions similar to those of the cell-free study (same detergent, buffers, and gradients), we typically observed a 6S sedimentation peak for Torpedo subunits and only obtained peaks >7S if the detergent to protein ratio was reduced (not shown); presumably this is due to insufficient solubilization.…”
Section: (G)contrasting
confidence: 99%
“…The 5S sedimentation of unassembled a suggests that newly synthesized subunits do not first associate as large homooligomers, although 5S is larger than expected for a monomer. In a series of cell-free translation studies, Anderson and Blobel (1983) found that each of the four Torpedo subunits formed large, apparently homooligomeric, complexes sedimenting broadly at '~,7-13S. Their data led them to propose that newly synthesized AChR subunits form homooligomers before associating with heterologous subunits.…”
mentioning
confidence: 99%
“…We cannot, therefore, rule out that the orientation achieved in the wheat germ cell-free system is different from that achieved in the brain. However, previous studies of membrane protein biogenesis in cell-free systems have demonstrated fidelity with the early events in living cells (1,21,23), and other studies of the scrapie agent are suggestive of an integral membrane protein (31,32,44 …”
Section: Discussionmentioning
confidence: 99%
“…In this respect, the recent observation (38) that all four subunits of Torpedo AcChoR can form homopolyers during biosynthesis and transport may ultimately lead to understanding how the selective glycosylation we discuss here is achieved.…”
Section: Discussionmentioning
confidence: 99%